Optimising Value Recovery in Closed-Loop Supply Chains through Analytical Models - Naghashan, Mona (2010)
The awareness of sustainable supply chain management has increased noticeably during the last decade. With this trend and economical, political and consumer forces, closed loop supply chain or reverse supply chain management has been evolved to help companies in identifying possible advantages and conquer challenges in their operations and strategies. The increasing attention to product reuse is not just due to environmental concerns and legislation but also the proven potential in profitability of reuse activities. This research puts forward an analytical approach to explore optimal closed-loop supply chain value recovery strategies. An analytical model can express the required parameters and factors that have direct or indirect impact on the company’s value recovery. The advantage of using the analytical models provided in this research is that they are widely applicable and not related to a specific industry or product range. An important factor in development of the models is the cost involved in each decision. Therefore, the best recovery policy in our cases is based on the minimum cost that emerges for the manufacturer. When considering different reuse alternatives, we found as more recovery options become available for companies, development of the optimum strategy turns out to be more complicated. In addition, the study has shown the dependency of value recovery on the demand profile, the returns rate (ρ), the residence time of products by the customer (L), and the secondary markets sale potential (f).